2019
DOI: 10.1016/j.csbj.2019.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation State Dependent Conformational Changes of HMGB1 Regulate the Formation of the CXCL12/HMGB1 Heterocomplex

Abstract: High-mobility Group Box 1 (HMGB1) is an abundant protein present in all mammalian cells and involved in several processes. During inflammation or tissue damage, HMGB1 is released in the extracellular space and, depending on its redox state, can form a heterocomplex with CXCL12. The heterocomplex acts exclusively via the chemokine receptor CXCR4 enhancing leukocyte recruitment. Here, we used multi-microsecond molecular dynamics (MD) simulations to elucidate the effect of the disulfide bond on the str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…CXCL12/CXCR4 antagonists have shown encouraging results in reducing the enhanced survival and proliferation of leukemia cells and sensitizing leukemia cells to chemotherapy [ 60 , 61 ]. During inflammation or tissue damage, extracellular fr-HMGB1 exerts chemotactic activity and enhances leukocyte recruitment by forming a heterocomplex with CXCL12 and binding to CXCR4 [ 31 , 62 , 63 ]. It has been found that the IKKα/noncanonical NF-κB pathway is required for sustained CXCL12/SDF-1 production to induce migration toward HMGB1, indicating that the heterocomplex of HMGB1 and CXCL12/SDF-1 may induce cell migration through the NF-κB pathway [ 64 ].…”
Section: Overview Of Hmgb1mentioning
confidence: 99%
“…CXCL12/CXCR4 antagonists have shown encouraging results in reducing the enhanced survival and proliferation of leukemia cells and sensitizing leukemia cells to chemotherapy [ 60 , 61 ]. During inflammation or tissue damage, extracellular fr-HMGB1 exerts chemotactic activity and enhances leukocyte recruitment by forming a heterocomplex with CXCL12 and binding to CXCR4 [ 31 , 62 , 63 ]. It has been found that the IKKα/noncanonical NF-κB pathway is required for sustained CXCL12/SDF-1 production to induce migration toward HMGB1, indicating that the heterocomplex of HMGB1 and CXCL12/SDF-1 may induce cell migration through the NF-κB pathway [ 64 ].…”
Section: Overview Of Hmgb1mentioning
confidence: 99%
“…2a Breaks the HMGB1•CXCL12 Heterocomplex NMR titrations and HADDOCK calculations indicate that 2a targets in part the region that has been shown to be involved in the interaction with CXCL12 (Schiraldi et al, 2012;De Leo et al, 2019;Fassi et al, 2019). We therefore asked whether 2a was able to interfere with the HMGB1•CXCL12 heterocomplex ( Figure 7A).…”
Section: D Model Of the Interactions Of 2a With Hmgb1 Boxesmentioning
confidence: 99%
“…Interference with this heterophilic interaction is attractive but challenging for several reasons: (i) the three-dimensional structure of the complex is still unknown, and (ii) the interaction surface is expected to be large and dynamic, thus difficult to be targeted by small molecules (Schiraldi et al, 2012;De Leo et al, 2019;Fassi et al, 2019). Previous work has shown that it is possible to interfere with the pro-inflammatory properties of HMGB1 using small molecules including glycyrrhizin (Mollica et al, 2007), salicylic acid (SA), and its derivative amorfrutin (Choi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This analysis disclosed that the HBP08 binding site on BoxA is formed by some residues Ala17, Val20, Arg24 and Glu25, important also for the CXCL12 binding. 13 Therefore, the peptide binding might antagonize by competition the formation of the CXCL12/HMGB1 heterocomplex.…”
Section: Characterization Of the Hmgb1-hbp08 Interactionmentioning
confidence: 99%
“…12 Reduced HMGB1, once released in the extracellular space, can form a heterocomplex with CXCL12 and synergistically promote, via CXCR4, the recruitment of leukocytes to inflammatory sites. 7,8,13 Moreover reduced HMGB1 can bind to the receptor for advanced glycation endproducts (RAGE) to induce CXCL12 secretion and authophagy. 14…”
Section: Introductionmentioning
confidence: 99%